A Nano‐Imaging Study of Graphene Edge Plasmons with Chirality‐Dependent Dispersions (Advanced Optical Materials 10/2021). Issue 10 (19th May 2021) - Wang, Ximiao; Zheng, Zebo; Xu, Ningsheng; Wang, Weiliang; Chen, Huanjun; Deng, Shaozhi
Abstract : The graphene plasmons at the edges of a monolayer graphene have been demonstrated to exhibit superior electromagnetic ?eld con?nements. In article number 2100207, Huanjun Chen and co‐workers show that, with a nano‐imaging technique, the edge plasmon modes at zigzag and armchair edges exhibit chirality‐dependent dispersions. In addition, due to the stronger molecule absorption ability of the zigzag edge, the associated plasmons exhibit a broader tuning range upon chemical doping via HNO3 exposure. This outcome highlights the potential of graphene zigzag edge in applications of nanoscale molecular sensing.